STUDENTS’ DIFFICULTIES OF INITIAL WRITING ABILITY OF ELEMENTARY STUDENTS DURING THE COVID-19 PANDEMIC - Dinda Aprillia Ayuningtyas, Zahara Tussoleha Rony, Suharjuddin (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2022)
In the observations that have been made by the researcher, the researcher chose the problem of difficulty in the beginning process of writing in class. Starting to write is considered as the basis for improving and developing students' abilities at the next level, so this study aims to find out the difficulties faced by researchers. experienced by students and find out the factors that cause students to have difficulty writing at the beginning. The method used in this research is qualitative with a case study approach where researchers want to know the writing difficulties that exist in class students and researchers want to know the factors causing difficulties in writing. Sources of data obtained from observations and interviews with students. Data Analysis and Interpretation Techniques in this study used the theory of Miles and Huberman with data reduction, data presentation, and conclusion drawing. The data of this research are in the form of words, phenomena, photos, attitudes, and daily behavior in schools which were obtained by researchers from observations, interviews, and documentation. This research can be used to see what factors cause difficulties. The findings of the study indicate that difficulties often experienced by students such as the use of capital letters, determining the distance of writing that there is still a distance between one letter and another, writing is incomplete, less proportional.